Knowledge of Risk Factors and Preventive Measures against Cervical Cancer among Female Students of Nnamdi Azikiwe University, Awka. - Echezona , Ejike Udokanma; Anthony Ikechukwu, Ogbalu (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Cervical cancer has continued to be a public health issue of great concern. This study investigated the knowledge of risk factors and preventive measures against cervical cancer among female students of Nnamdi Azikiwe University, Awka (UNIZIK). The descriptive survey research design was adopted for the study. The population consisted of 2398 final year (2010/2011 set) female students from all (10) the faculties in Nnamdi Azikiwe University, Awka campus. A sample of 350 female students was drawn from two faculties selected using purposive sampling technique and used for the study. Convenient sampling technique was however, employed in the administration of the instrument. A structured questionnaire named Knowledge of Risk Factors and Preventive Measures Against Cervical Cancer Questionnaire (KRPACQ) was the instrument used for data collection. The instrument was validated and the test-retest reliability value obtained using Pearson Product Moment Correlation Co-efficient was 0.82. Descriptive statistics of frequency and percentage (%) were used to analyze the data collected from 328 copies of the questionnaire found analyzable and represented with tables and bar chart. Ashurscale was used as a criterion for assessing the knowledge of the respondents. The findings show that there is a high knowledge of cervical cancer and low knowledge on cause, risk factors and preventive measures for cervical cancer amongst the respondents. Based on this, it was recommended that education of the female students in the different levels of education in various institutions of learning on cervical cancer cause, risk factors and preventive measures should be intensified.